Kepribadian Tokoh Meirose dalam Film Surga yang Tak Dirindukan (Kajian Psikologi Humanistik Abraham Maslow) - Novia Permata Silviandari; Redyanto Noor (Universitas Mulawarman, 2023)
This research aims to analyze the personality of the character Meirose in the film Surga yang Tak Dirindukan based on Abraham Maslow's theory of humanistic psychology. The approach used in this study is a literary psychology approach. The auxiliary theory used is Abraham Maslow's theory of humanistic psychology. The research method used is descriptive qualitative with the type of library research. The research results show that Meirose's character in Surga yang Tak Dirindukan film has a drastic personality change. Meirose's character at the story's beginning is easily discouraged, moody, and vindictive. It occurs due to physiological needs not being met, safety needs, love and belonging needs, esteem needs and self-actualization needs. By not fulfilling physiological and psychological needs, Meirose's character experiences a mental shock that makes her try to fulfil all her needs. One of the things that can help meet Meirose's needs is to become the second wife of the character Prasetya. Meirose's physiological needs are met after becoming Prasetya's wife. Even so, her psychological needs have not been completely fulfilled because of his status as a second wife. Meirose's personality becomes patient, religious, and strong by meeting physiological and psychological needs.